2009
DOI: 10.1029/2009ja014163
|View full text |Cite
|
Sign up to set email alerts
|

Propagation characteristics of Pi 2 pulsations observed at high‐ and low‐latitude MAGDAS/CPMN stations: A statistical study

Abstract: [1] The objective of this study is to understand better the propagation of Pi 2 waves in the nighttime region. We examined Pi 2 oscillations that showed high correlation between high-and low-latitude Magnetic Data Acquisition System/Circum Pan-Pacific Magnetometer Network stations (correlation coefficient: jgj ! 0.75). For each horizontal component (H and D) we examined the magnetic local time (MLT) dependence of the delay time of high-latitude Pi 2 oscillations that corresponds to the highest correlation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
75
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(89 citation statements)
references
References 44 publications
14
75
0
Order By: Relevance
“…The shift values were the delay time for the maximum correlation coefficient between GAM H and each station's H. Correlation coefficients were calculated for the interval from 10:18:00 to 10:30:00 UT. The correlation coefficients for each station were TIK: 0.90, CHD: 0.81, ZYK: 0.92, MGD: 0.93, respectively (i.e., high-correlation Pi2 [Uozumi et al, 2009]). Figure 5 clearly shows that after the phase shift completed, the relative phase differences kept among stations until the end of the Pi2 event.…”
Section: The 24 January 1997 Eventmentioning
confidence: 99%
See 4 more Smart Citations
“…The shift values were the delay time for the maximum correlation coefficient between GAM H and each station's H. Correlation coefficients were calculated for the interval from 10:18:00 to 10:30:00 UT. The correlation coefficients for each station were TIK: 0.90, CHD: 0.81, ZYK: 0.92, MGD: 0.93, respectively (i.e., high-correlation Pi2 [Uozumi et al, 2009]). Figure 5 clearly shows that after the phase shift completed, the relative phase differences kept among stations until the end of the Pi2 event.…”
Section: The 24 January 1997 Eventmentioning
confidence: 99%
“…On the other hand, they found that in the premidnight sector the highlatitude H oscillation tended to delay from the low-latitude H oscillation (DT < 100 s) despite they were highly correlated each other. To explain the delay time, Uozumi et al [2009] developed a Pi2 propagation model in the magnetosphere, and confirmed that observed delay times were basically explained by the model estimation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations